Rab GTPase regulation of bacteria and protozoa phagocytosis occurs through the modulation of phagocytic receptor surface expression - Seixas, E. (2018)
This work was supported by Fundacao para a Ciencia e a Tecnologia (FCT) I.P., Portugal through grant PTDC/SAU-MII/104622/2008 (to M.C.S. and D.C.B.); the FCT Investigator Program (IF/00501/2014/CP1252/CT0001, to D.C.B.); and FCT post-doctoral fellowships SFRH/BPD/34094/2006 (to E.S.) and SFRH/BPD/78491/2011 (to C.E.).